Time of the child [large type] - Williams, Niall, 1958- (Thorndike Press large print top shelf., 2024)
"Doctor Jack Troy was born and raised in the little town of Faha, but his responsibilities for the sick and his care for the dying mean he has always been set apart his community. A visit from the doctor is always a sign of bad things to come. His daughter, Ronnie, has grown up in her father's shadow, and remains there, having and passed up an offer of marriage from an unsuitable man. But in 1962, as the town readies itself for Christmas, Ronnie and Doctor Troy's lives are turned upside down when a baby is left in their care. As the winter passes, father and daughter's lives, the understanding of their family, and their role in their community are changed forever"--